DAMPAK FISIK KENAIKAN MUKA AIR LAUT TERHADAP WILAYAH PESISIR KOTA MEDAN KECAMATAN MEDAN BELAWAN Physical Impacts of Sea Level Rise on Coastal Areas of Medan Belawan - Tri Woro Widyastuti; Darma Bakti; Zulham Apandy Harahap (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2015)
Tidal flood case is a problem that often happens in coastal areas. This happens because of the surface of the ground low or even the same compared to the surface of sea water. Besides that, this can also happens due to the increase of sea levels so that when there is a tide the sea water will come and flooded the coastal areas. The purpose of this research is to analyze the condition of tide in coastal areas of Medan city in Medan Belawan sub district and provide a map vulnerability to the increase of sea levels in Medan city. The number of increasing sea levels is obtained from the average of increase tidal per year. This number then will be associated with land use data, topography data, population data, and also direct interview with the local residents. After that, VCA method will be used based on PERKA BNPB N0. 2 the year 2012 to acquire the class vulnerability in each village and projected into the form of map with overlay method. The result of this research showed that the inundation area caused by the increase of sea levels always rising. Based from the VCA method and direct interview, resulted that most of vulnerability that happens in Medan Belawan sub district is belong to the high vulnerability. This result is also suitable with map vulnerability made by BNPB that stating North Sumatera is belonging in category of high vulnerability class. Therefore it needs further treatment to decrease the effect of the increasing sea levels.Keyword : Sea Level Rise, Rob, VCA method.